The "how to" grants manual ebook Successful grantseeking techniques for obtaining public and private grants. - Bauer, David G. (2021)
This book provides the user with a system for pre-determining the likelihood of grants success before investing time in proposal preparation. The exhibits, tables and figures keep new and veteran grantseekers focused on the process and on obtaining the critical information they need to decide whether to complete a proposal. The interactive exhibits that are downloadable provide the worksheets users needs to win grants This book shows readers how and when to use the research they gather on prospective grantors to increase their chances of success. Instruction is provided on why and how to gather information on past grantees, scoring systems, and reviewers, and on how to make preproposal contact to dramatically increase success rates. The deceptively simple techniques outlined in the exhibits, and the use of the project planner to present an orderly proposal in a timely manner, are worth the whole investment in the book. Bauer does not start with how to write a grant, but rather how proposal development fits the grantseeker's career plan, and relates to the mission of his or her nonprofit, university, college, department or program. The emphasis on the book is not on money, but on creating a winning match between the grantor, the grantee, and his or her institution/organization. The reader is provided with strategies and techniques to create strong teams, build productive consortia, and match grantseeking tasks to group member skills. This is particularly relevant now given grantors' growing interest in funding interdisciplinary and multiple site projects and research that uses grant monies more efficiently. Those readers that teach or coach grantseeking will also find strategies in the book that are essential to creating success for others in the grants process. As the hunt for grants gets more competitive and hectic, the need for a system that uses time effectively and provides organizational techniques and other strategies for increasing grants success rates, is critical. The step-by step process presented in the book plus the free downloadable worksheets make the purchase of this book a very cost-effective investment.